PATTERN-RECONFIGURABLE ANTENNA FOR 5.5-GHZ WIMAX APPLICATIONS - AHMED, FAYYADH H. (Journal of Duhok University, 2017)
Pattern reconfigurable antenna, which is based on multi-switchable radiators with rectangular reflectors, is presented. The antenna utilized the self-similarity double ring configuration property in the form of rectangular and a Wilkinson power divider feeder, to exhibit wideband and radiation pattern reconfiguration characteristics. The pattern reconfiguration is achieved by feeding these self-similarity double rings of antenna in two directions. A few switches and power divider is used in order to change the feeding direction.The antenna is capable of steering the beam in the four directions 25˚, 52˚, 155˚ and 158˚ in the azimuth plane and, four directions 20˚, 10˚, 5˚, and 51˚ in the elevation plane, depending on the state of switches loaded on the rectangular rings. Initial results were obtained by using short and open circuits to represent ON and OFF for switches respectively. The proposed reconfigurable antenna has the advantage of miniaturization, simple reconfigurable, low profile, light weight, and easy fabrication. For verification of simulation results, the proposed antenna is fabricated and the prototype is measured using R&S ZVL 13 Vector Network Analyzer. The results show a good agreement between simulated and measured results.